Posisi Ahli Waris Pengganti Dalam Pembagian Harta Perspektif KHI dan KUH Perdata - Agista Tamia Putri; Samsul Arifin (Faculty of Law Universitas Muhammadiyah Metro, 2025)
This study aimed to determine the system of surrogate inheritans according to the Compilation of Islamic Law and the Civil Law Book and to determine the comparison of the surrogate inheritans according to the Compilation of Islamic Law and the Civil Law Book. The research method used in this research was normative study. The results of this study are that: 1. The inheritance system in the perspective of Islamic law is based on the provisions Article of 185 in the compilation of Islamic Law, paragraph (1), said that a grandson can act as a surrogate inheritan to replace the position of his parents who have died more before the inheritan himself. In the inheritance system in the Civil Law Book, found the three types of place replacement systems, namely: downward line replacement, sideways line replacement, and deviated line replacement in which contained in the articles of 842-845 of the Civil Law Book. 2. The comparative law regarding to the surrogate inheritans according to the Compilation of Islamic Law: That children who take the place of their parents are sons and daughters from the male lineages whose parents have died earlier than the inheritan him/herself, while boys and girls from the female lineages are not entitled to replace their mother's position in obtaining the property of their grandfather. According to the Civil Law Book: That the child who replaces his father's position may be from the male lineages or from the female lineages. The most important thing is that the person that being replaced has passed away earlier than the inheritan and he (the person that being replaced) is the liaison between his son (who replaced his father's position) with the inheritan.